Planning in Cape Towns interstices: case studies of informal land occupations in Cape Town, South Africa - Ngwenya, Nobukhosi (School of Architecture, Planning and Geomatics, 2023)
Participatory planning has been institutionalised through planning legislation in most Western-style democracies since the 1940s. Irrespective of the variability in how participation is conducted in different contexts, participation is regarded as desirable. That is, provided participation activities and processes do not flout laws or infringe the property rights of others in the manner that informal land occupations do. Often characterised as a problem, informal land (whereby land is defined broadly to include vacant and under-utilised buildings) occupations and, consequently, the numbers of autoconstructed and retrofitted housing have not only continued apace since 1994 in South Africa, they have intensified in scale, frequency, and level of organisation. The aim of this research is to develop a theoretical understanding of informal land occupations from the residents' (read occupiers') perspectives. These citizen-led place making practices, which have not yet been fully theorised in Southern planning literature, constitute the issue under study. Thus, the main research question is: What strategies and tactics are used by residents to claim and sustain urban spaces in Cape Town, South Africa? To answer this question, the research employed the case study and discourse analysis methods. The four cases for this research were located in Green Point, Woodstock, and Khayelitsha. Fourteen (14) semi-structured interviews and five (5) focus groups were conducted to gain the perspectives of a range of actors in the spatial planning and human settlements sectors, namely occupiers, professional planners working within local government and non-government organisations (NGOs), activists, elected local government officials, and bureaucrats within local and provincial government departments. Additional data in the form of government publications, namely policy documents, legislation, and transcripts of Parliamentary debates and Council meeting minutes to mention a few, as well as photographs, media statements and articles was also collected in the period between 2016 and 2022. This data was analysed through an iterative cycle of open, axial and selective coding. The findings indicate that residents claim spaces, namely land and building, that are perceived to be vacant or underutilised. These spaces, which whilst requiring the (re)construction of housing or retrofitting, are suitable for a range of land uses. These spaces are residual in nature, nonsynchronous, accommodate new or atypical performances, create uncertainty and new rules. These spaces are claimed through bold, bi-directional discursive and physical strategies and tactics. Occupations are initiated through mobilisation, which continues for the occupation's lifespan in order to re-mobilise existing residents and to mobilise (additional)support and resourcesfor the movement. Once the occupation is under way, autoconstruction, retrofitting, repair, and maintenance activities are undertaken. These activities, along with discursive strategies and performative repertoires, enable residents to sustain their claims. The findings also highlight that these processes occur in the city's interstices, with many of these spaces being left vacant or underutilised as a result of the city's growth. Within these spaces of possibility, residents' visionsforthe city are ineffectively realised. These visions are based on inherited imaginations that, in turn, are founded on both Western and African philosophical and theological currents. And, it is from this intellectual foundation that the radicality of informal land occupations emerges. On this intellectual foundation, residents strive to foster an African sense of self, re-affirm their humanity and dignity whilst highlighting alternative solutions for dealing with their current reality.